2008
DOI: 10.1097/sla.0b013e318167748c
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Benefits of Roux-en-Y Pouch Reconstruction After Total Gastrectomy

Abstract: Roux-en-Y pouch reconstruction after gastrectomy is simple to perform and safe. Long-term survivors benefit from pouch reconstruction. Therefore, a pouch is recommended for patients with a good prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
3
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(94 citation statements)
references
References 24 publications
3
83
3
5
Order By: Relevance
“…Previous studies reported that BWL after gastrectomy was approximately 10-20 % of the preoperative weight [3]. For example, Noguchi et al [17] evaluated 97 patients who had undergone gastrectomy, and found that the mean body weight at discharge was 79 ± 7 % in the total gastrectomy group and 84 ± 7 % in the distal gastrectomy group This discrepancy could be explained by the following factors.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous studies reported that BWL after gastrectomy was approximately 10-20 % of the preoperative weight [3]. For example, Noguchi et al [17] evaluated 97 patients who had undergone gastrectomy, and found that the mean body weight at discharge was 79 ± 7 % in the total gastrectomy group and 84 ± 7 % in the distal gastrectomy group This discrepancy could be explained by the following factors.…”
Section: Discussionmentioning
confidence: 58%
“…Body weight loss (BWL) is a common problem after gastrectomy for gastric cancer, and occurs during the initial 1-3 months after surgery [2]. Previous studies demonstrated that BWL after gastrectomy was approximately 10-20 % of the preoperative body weight [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although various mechanisms have been considered, such as the perturbation of absorption due to reduced pancreatic excretion [4,5], a decrease in the gastric acid level [6], reflux esophagitis [7], intestinal floral alteration [8], and increased peristalsis and diarrhea [9], reduced food intake [10,11] is the most conceivable explanation for weight loss after gastrectomy. To combat loss of appetite, surgeons dealing with gastric cancers have tried to increase food intake by producing a gastric substitute, such as a jejunal pouch, with limited success [12]. However, we frequently observe that patients do not exhibit significant weight loss after total gastrectomy when they resort to small but frequent meals.…”
Section: Introductionmentioning
confidence: 99%
“…The length of the incision on the stomach is important for avoiding stenosis, because it determines the size of the stoma. The mean percent body weight loss in our patients at 12 months after surgery was 10 %, which seems to be less than that with total gastrectomy [16,17]. Although the nutritional status was not examined in detail in this study, proximal gastrectomy may also benefit patients from the nutritional point of view.…”
Section: Discussionmentioning
confidence: 79%